Where do you sell your products online? A seller perspective on online shopping platforms - Saerom Lee; Min Ho Ryu; Sang Yup Lee; Dong-Heon Kwak (International Telecommunications Society (ITS), 2018)
With the rapid development of information and communication technologies, various online shopping platforms have emerged. To understand the success of platform strategies, it is important to verify the features that are important to attract sellers. To estimate the economic value of free platforms for sellers, we try to estimate the willingness to pay (WTP) for each feature. Based on the features provided by Naver Smart Store (https://sell.smartstore.naver.com), we conduct a conjoint analysis. Notably, since Naver Smart Store platform provides the platform service for free to sellers as an open platform strategy, we can anticipate that the results of this research will reveal the value of an open platform strategy.
Keywords: 330; Digital Platform; Online Platform Strategies; Commerce Market; Conjoint Analysis; Willingness to Pay